Aditivo a base de leveduras e óleos essenciais na dieta de novilhos confinados submetidos a diferentes níveis nutricionais na recria - Gaspar, Renato Guedes (2019)
This work was carried out with the objective of evaluating the effects of the nutritional level in the rearing phase and addition of the commercial product with yeast and vegetal oils in the feedlot diet on the productive performance of steers. Twenty-four steers with initial body weight of 423.65 kg and initial age of 18 months were used. The animals were submitted to different nutritional levels in the rearing phase, characterized by three levels of supplementation: mineral salt at will and supplements formulated for consumption of 1.5 and 4 g/kg body weight. At the end of the rearing phase the animals were confined and fed a diet containing 77.73% of concentrate and 22.27% of roughage (corn silage) with or without inclusion of commercial product based on yeasts and vegetable oils (50g/animal/day). The animals were slaughtered with 479.96 kg of body weight. The experimental design was completely randomized, with treatments in 3 x 2 factorial arrangement (three nutritional levels in the rearing and two diets), using 4 replicates. The nutritional levels in the rearing phase did not alter the nutrient intake, carcass (except the physical composition) and meat characteristics. The animals supplemented with supplements formulated for consumption of 4g/kg body weight during the rearing period allowed a higher average daily gain during the confinement termination period. The inclusion of the additive with yeasts and vegetable oils allowed carcasses with greater amount of muscle and smaller quantity of fat. However, when the carcass tissues were expressed as % of carcass weight, the differences between diets for the physical composition disappeared. Supplementary strategies in the rearing phase that allow moderate feed intake (4 g/kg of body weight) in relation to supplementation with mineral salt or supplements with low consumption (at 1.5g/kg of body weight), allow for greater weight gain of steers fed in confinement with diets containing high content concentrate for a short period of time. Additives based on yeasts and vegetable oils in high concentrate diets do not alter the productive performance of confined steers for a short period of time.